Lyapunov stability and weak attraction for control systems - Rocha, Victor H. L. [UNESP] (2022)
In this paper we deal with Lyapunov stability and weak attraction for control systems. We give characterizations of the stability and asymptotical stability of a compact set by means of its components. We also study the asymptotical stability of the prolongation of a compact weak attractor